Detection the Dust Storms Using MODIS Reflection Mode - Jalal, Fatima; Mahdi, Alaa S. (Iraqi Journal of Science, 2024)
In previous years, most regions of the Middle East suffered from frequent dust storms, Iraq at the top of that where Iraq was classified as the fifth most vulnerable country to climate change according to the Paris Climate Agreement; the frequent dust storms are considered the most prominent effects of climate change, which are a result of lack of rain and drought, and thus desertification and desertification. The storms appear when the winds blow. This research reviews using of space data, MODIS (Moderate Resolution Imaging Spectroradiometer, satellite images), and its two platforms, Terra and Aqua, to monitor storms movement and determine the starting point source using the PCA (Principal Component Analysis algorithm) in ENVI and sub-software MATLAB for (MOD09GA) and (MYD09GA) that represents the reflectivity daily monitoring, the first layer from HDF file of MODIS data red band, 620-670 nm, was used. The period was studied in research in May of 2022 with the kernel of PCA containing five bands represented by the day of the storm and two days before and after the storm for the study area located Coordinates: 35.0468, 43.0305. The results determined that the source of dust storms are cross-border storms that are not local in origin; the estimated area of the storm that covered large regions of Iraq by (351353.45) km2 for 2022-5-5, (308024.9.km2) for the day 2022-5-16 and with an estimated area (326933.35 km2) for the day 2022-5-23.